Peer navigation-delivered loving kindness meditation: A pilot project - Alyson Moadel-Robblee; Fernando Camacho; Gabrielle E. Milner; Alexander Kertzner; Nicolas F. Schlecht (Elsevier, 2021)
Peer navigators (PNs), including trained cancer survivor volunteers, can be an important resource to the cancer care team in reducing barriers to screening, treatment, and psychosocial care among underserved communities through their roles in outreach, education, advocacy, and peer support. As cancer centers face growing patient demand and evidence for integrating complementary therapies into conventional care, opportunities to envision new roles for PN arise. Based on psychosocial assessments conducted at an academic cancer center serving the low-income population of Bronx, NY, we found strong interest in both providing (44 %) and receiving (76 %) peer support, as well as in (76 %) mind-body practices (e.g., meditation). In research, these mind-body modalities and peer support have both been found to improve many aspects of physical and emotional outcomes in cancer patients, but none has looked at PNs as a potential resource for delivering such mind-body interventions. Towards this end, we conducted two pilot studies to train PN from an onsite peer navigation program called the BOLD Buddy Program, to deliver a well-defined, easy to learn, and culturally-aligned mind-body practice, i.e., Loving Kindness (LK) Meditation, to each other and to patients. Incorporating comparison to professional meditation instructors, our pilot work demonstrated that peer-lead LKM was associated with benefits to emotional well-being, relaxation, satisfaction, and perceived usability and that PNs were equally well-received in delivering LK as their professional counterparts. Evaluating 8 domains of feasibility using standardized measures, we were able to demonstrate that peer-lead LK was: in demand, acceptable, implementable, practical, adaptable, adoptable, expandable, and promising in efficacy.